Pilot Study on the Effects of Music-making on Cortisol, Alpha-amylase and Immunoglobulin-a Among Older Amateur Musicians - Barbeau, Audrey-Kristel (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2024)
There are many benefits associated with playing music in later life but few studies have looked at biomarkers of stress and immune response among musicians. A pilot study, undertaken to test a research protocol prior to a larger study, was carried out with eight amateur instrumentalists aged 50+ to investigate variations in stress (cortisol and alpha-amylase) and immune response (secretory immunoglobulin A) under two conditions (Music and Rest). In summary, cortisol levels tend to decline following both conditions, but results were more pronounced for the Rest condition. While sIgA increased in the Rest condition, it showed a larger variability in the Music condition. These results are promising and demonstrate that music can influence some biological markers. This study contributes to raising awareness that music can be a creative strategy to promote healthy aging.